The Preclinical Benefit of Glutamine in bisphenol A-induced Hepatotoxicity in Wistar Rats - Ben Enoluomen Ehigiator; Theodore Mmamsichukwu Ajaekwe; Elias Adikwu (Mazandaran University of Medical Sciences, 2023)
Background: Oxidative stress may be a causative factor for bisphenol A (BPA) -induced hepatotoxicity. Glutamine (GM) is an amino acid with the ability to inhibit oxidative stress.  Objective: This study evaluated the ability of GM to prevent BPA-induced hepatotoxicity in rats.  Methods: Adult Wistar rats of both sexes (n=30) were used. The rats were randomly grouped into six of five rats each. Groups A (Control), B, and C were treated with normal saline (0.2 mL), GM (80 mg/kg), and BPA (50 mg/kg), respectively for 60 days. Groups D-F were treated with GM (20 mg/kg)+BPA (50 mg/kg), GM (40 mg/kg)+BPA (50 mg/kg), and GM (80 mg/kg)+BPA (50 mg/kg), respectively for 60 days. After treatment, blood and liver samples were obtained for biochemical and histological assessments, respectively.  Results: Significantly (P<0.01) decreased body weight and significantly (P<0.01) increased liver weight occurred in the BPA-administered group when compared to the control group. The BPA-administered group showed significantly (P<0.001) elevated serum total bilirubin, lactate dehydrogenase, aminotransferases, conjugated bilirubin, gamma-glutamyl transferase, alkaline phosphatase, and liver malondialdehyde concentrations when compared to the control group. Significantly (P<0.001) decreased liver superoxide dismutase, glutathione peroxidase, catalase, and glutathione levels occurred in the PBA-administered group when compared to the control group. BPA caused hepatocyte necrosis, sinusoids, and central vein congestion. BPA-induced hepatotoxicity was reversed by GM; 20 mg/kg (P<0.05), 40 mg/kg (P<0.01), and 80 mg/kg (P<0.001) in a dose-related fashion when compared to BPA.  Conclusion: GM may be effective against BPA-associated hepatotoxicity.